Damage in dual phase steel DP1000 investigated using digital image correlation and microstructure simulation. (9th October 2015) - Alharbi, Khaled; Ghadbeigi, Hassan; Efthymiadis, Panos; Zanganeh, Mohammad; Celotto, Steven; Dashwood, Richard; Pinna, Christophe
Abstract: Microstructure failure mechanisms and void nucleation in dual-phase (DP) steels during deformation have been studied using a combination of in situ tensile testing in a scanning electron microscope (SEM), digital image correlation (DIC) and finite element (FE) modelling. SEM images acquired during in situ tests were used to follow the evolution of damage within the microstructure of a DP1000 steel. From these images, strain maps were generated using DIC and used as boundary conditions for a FE model to investigate the stress state of martensite and ferrite before the onset of the martensite phase cracking. Based on the simulation results, a maximum principal stress of about 1700 MPa has been estimated for crack initiation in the martensite of the investigated DP1000 steel. The SEM image observations in combination with the FE analyses provide new insights for the development of physically-based damage models for DP-steels.